The Ethical Literature: Religion and Political Authority as Brothers - Feldman, Noah (Journal of Persianate studies, 2012)
Abstract This essay discusses the contribution of the Muslim ethical literature of the middle ages to Islamic political thought. The ethical literature offers a perspective on the medieval Islamic constitution that differs markedly from the picture that derives from the juristic literature on the caliphate. Where the juristic literature largely portrays political authority as the servant of religion, the ethical literature presents religion and political authority as “brothers” arrayed in a relationship of mutual dependence. This view is decisively influenced by pre-Islamic Iranian thinking on the relationship between religion and politics, as contained in the “Letter of Tansar.”